2021
DOI: 10.1136/bmjopen-2020-041894
|View full text |Cite
|
Sign up to set email alerts
|

Scoping review protocol: bladder cancer in Nigeria: what are the gaps in clinical care and research?

Abstract: IntroductionBladder cancer (BC) is the 10th common cancer worldwide and ranks seventh in Nigeria. This scoping review aims to identify the gaps in clinical care and research of BC in Nigeria as part of the development of a larger national research programme aiming to improve outcomes and care of BC.Methods and analysisThis review will be conducted according to Arksey and O’Malley scoping review methodology framework. The following electronic databases will be searched: Medline (using the PubMed interface), Ovi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Preferred Reporting Items for Systematic Reviews and Meta-Analyses-Scoping Reviews extension for scoping reviews 18 were followed to ensure all suggested items were reported. A detailed protocol of this scoping review has been published previously 19 and a brief summary is presented in figure 1.…”
Section: Methodsmentioning
confidence: 99%
“…Preferred Reporting Items for Systematic Reviews and Meta-Analyses-Scoping Reviews extension for scoping reviews 18 were followed to ensure all suggested items were reported. A detailed protocol of this scoping review has been published previously 19 and a brief summary is presented in figure 1.…”
Section: Methodsmentioning
confidence: 99%
“…Patients with early superficial bladder cancer have a 5-year recurrence rate of 60% to 80%, while patients with muscle-invasive bladder cancer have a 5-year mortality rate of 65%. [1] Conventional treatments with advanced bladder cancer have many side effects, poor drug resistance, and limited efficacy, causing great pain to patients. [2][3][4] Therefore, there is an urgent need for a patientderived in vitro tumor model as a preclinical tool to guide personalized patient treatment.…”
Section: Introductionmentioning
confidence: 99%
“…A PPI coordinator has the essential role of bridging between researchers, patients and the public [7]. Our PPI coordinator has been supporting a wide variety of studies, especially those where discussion meetings are needed to inform the study design or those where a consultation phase is required as part of, for example, a scoping review [8,9]. Even though most cancer researchers recognize the importance of PPI/E, it is not always possible or easy to include it in their research strategy.…”
mentioning
confidence: 99%